A photothermal super-hydrophobic anti-icing composite coating and a preparation method and application thereof
Patent Information
- Application Number
- CN202611280552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明的目的在于提供一种光热超疏水防覆冰复合涂层及其制备方法和应用,该复合涂层通过将高效光热转换组分与稳定的超疏水微纳结构有效结合,克服了现有涂层光热效率低、疏水稳定性差的问题,实现了被动防冰与主动除冰的协同增效
1、本发明提供的光热超疏水防覆冰复合涂层,是由依次涂覆于基底上的WO2.9/CNTs复合光热填料层和PMMA@SiO2核壳结构疏水颗粒层复合而成。所述WO2.9/CNTs复合光热填料作为光热转换中心,利用WO2.9的氧空位缺陷与CNTs的宽谱吸收特性,实现了高效的太阳光捕获与光热转换。所述PMMA@SiO2核壳结构表面接枝有十六烷基三甲氧基硅烷(HDTMS)作为疏水改性剂,通过水解缩合反应引入低表面能的长链烷基基团,使涂层表面呈现超疏水特性,水接触角大于150°,滚动角小于10°。所述复合涂层表面具有微纳粗糙结构,通过光热效应与超疏水效应的协同作用实现防覆冰功能。
Smart Images

Figure CN122978764A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional coating materials and surface protection technology, specifically to a photothermal superhydrophobic anti-icing composite coating, its preparation method, and its application. Background Technology
[0002] With global climate change and the increasing frequency of extreme weather events, surface icing poses a serious threat to the safe operation of power transmission, transportation, wind power generation, and communication facilities. Icing can lead to problems such as power line breaks and tower collapses, reduced lift on aircraft wings, and increased loads on wind turbine blades. Therefore, developing efficient, energy-saving, and environmentally friendly anti-icing and de-icing technologies is of significant practical importance. Existing anti-icing and de-icing technologies mainly include thermal de-icing, mechanical de-icing, chemical de-icing, and anti-icing coatings. Among these, thermal de-icing consumes a huge amount of energy, mechanical de-icing is inefficient and easily damages equipment surfaces, and chemical de-icing agents pollute the environment. In contrast, superhydrophobic coating technology has attracted much attention due to its passive water-repellent and delayed icing characteristics, becoming one of the effective means of controlling surface icing.
[0003] However, anti-icing coatings relying solely on superhydrophobic properties often face the risk of failure in extreme low-temperature and high-humidity environments. When the ambient temperature is too low or the impact velocity of supercooled water droplets is too high, the superhydrophobic surface cannot completely prevent the nucleation and growth of ice crystals, and once the ice layer forms, its adhesion to the surface remains strong, making it difficult to remove. To overcome this bottleneck, incorporating photothermal effects into superhydrophobic coatings, utilizing the material's ability to absorb sunlight and convert it into heat energy, to achieve synergistic anti-icing and de-icing effects of "photothermal + superhydrophobicity," has become a current research hotspot.
[0004] In the field of photothermal materials, non-stoichiometric tungsten oxide (WO2.9) exhibits excellent localized surface plasmon resonance (LSPR) due to its unique oxygen vacancy structure, enabling efficient light absorption and heat conversion in the near-infrared region. However, single-component photothermal materials often suffer from limited light absorption range and high carrier recombination rates, restricting further improvements in their photothermal conversion efficiency. Carbon nanotubes, as typical one-dimensional carbon nanomaterials, possess broad-spectrum light absorption characteristics, extremely high thermal conductivity, and chemical stability. Combining them with WO2.9 holds promise for constructing efficient electron transport channels, enhancing light absorption capabilities, and thus achieving more efficient interfacial photothermal conversion.
[0005] On the other hand, constructing superhydrophobic surfaces requires simultaneously satisfying low surface energy and suitable micro / nano rough structures. Currently, commonly used hydrophobic modifiers such as hexadecyltrimethoxysilane (HDTMS) can significantly reduce the surface energy of materials, while the core-shell structure formed by polymethyl methacrylate (PMMA) and silica (SiO2) can provide good film-forming properties and construct stable micro / nano rough structures through the rigid shell of SiO2. Although existing research has explored photothermal materials and superhydrophobic surfaces extensively, how to organically combine efficient photothermal conversion components with stable superhydrophobic micro / nano structures to prepare anti-icing coatings with excellent photothermal heating performance, high hydrophobicity, and environmental stability remains a pressing technical challenge. In practical applications, existing coating materials often suffer from poor compatibility between components, easy damage to the rough structure, or hydrophobicity degradation under harsh environments, resulting in short-lasting anti-icing effects and failing to meet the needs of practical engineering applications. Summary of the Invention
[0006] The purpose of this invention is to provide a photothermal superhydrophobic anti-icing composite coating, its preparation method and application. This composite coating effectively combines a high-efficiency photothermal conversion component with a stable superhydrophobic micro / nano structure, overcoming the problems of low photothermal efficiency and poor hydrophobic stability of existing coatings, and achieving synergistic effect of passive anti-icing and active de-icing.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A photothermal superhydrophobic anti-icing composite coating is composed of a filler layer and a hydrophobic particle layer sequentially coated on a substrate. The filler layer is made of WO3. 2.9 The CNTs composite photothermal filler is composed of hydrophobic particle layers made of PMMA@SiO2 core-shell structured hydrophobic particles with surface grafted hexadecyltrimethoxysilane (HDTMS); the WO 2.9 / CNTs composite photothermal filler serves as the photothermal conversion center, and hexadecyltrimethoxysilane (HDTMS) on the surface of the PMMA@SiO2 core-shell hydrophobic particles serves as the hydrophobic modifier; the surface of the composite coating has a micro-nano rough structure, and achieves anti-icing function through the synergistic effect of photothermal effect and superhydrophobic effect.
[0008] Furthermore, the WO 2.9 / CNTs composite photothermal filler is made of WO 2.9 It is composed of CNTs, of which WO 2.9 The WO3 is a non-stoichiometric tungsten oxide with an oxygen vacancy defect structure; CNTs are carbon nanotubes, serving as the thermally conductive framework and light absorption enhancement component of the composite coating; the WO3... 2.9 The carbon nanotube content in the CNTs composite photothermal filler is 15-30 wt.% to ensure that the coating has good photothermal heating performance.
[0009] Furthermore, the PMMA@SiO2 core-shell structured hydrophobic particles with hexadecyltrimethoxysilane (HDTMS) grafted onto their surface have polymethyl methacrylate (PMMA) microspheres as the core and silica (SiO2) as the shell, with hexadecyltrimethoxysilane (HDTMS) grafted onto the surface of the silica (SiO2) shell; the thickness of the SiO2 shell is at the nanometer level, which is used to construct the surface roughness.
[0010] Furthermore, the polymethyl methacrylate (PMMA) microspheres have a size of 80-120 nm, and the SiO2 shell has a thickness of 10-50 nm.
[0011] Furthermore, the hexadecyltrimethoxysilane (HDTMS) is grafted onto the surface of the SiO2 shell layer of the PMMA@SiO2 core-shell structure through a hydrolysis-condensation reaction, introducing long-chain alkyl groups with low surface energy, so that the coating surface exhibits superhydrophobic properties, with a water contact angle greater than 150° and a roll-off angle less than 10°.
[0012] Furthermore, in this composite coating, the filler layer has a thickness of 1-3 mm, and the hydrophobic particle layer has a thickness of 20-50 μm.
[0013] The method for preparing the photothermal superhydrophobic anti-icing composite coating includes the following steps: (1) Preparation of WO 2.9 / CNTs composite photothermal filler: CNTs are dispersed in anhydrous ethanol, and WO3 is added. 2.9 The mixture was ultrasonically stirred until homogeneous; the resulting mixture was then washed and dried to obtain WO3. 2.9 / CNTs composite photothermal filler; WO 2.9 Mechanically combined with CNTs to improve photothermal conversion efficiency; (2) Preparation of HDTMS-modified PMMA@SiO2 core-shell hydrophobic particles: First, PMMA@SiO2 core-shell structures were prepared by sol-gel method, and then hexadecyltrimethoxysilane (HDTMS) was grafted onto the surface of the core-shell structure by hydrolysis-condensation reaction. The specific process is as follows: polymethyl methacrylate (PMMA) microspheres were dispersed in an ethanol-water mixed solvent, and ammonia was added to adjust the pH to 9-10 to obtain a PMMA dispersion. Ethanol solution of tetraethyl orthosilicate (TEOS) was slowly added to the PMMA dispersion under water bath conditions of 25-35℃ to carry out the reaction and obtain a PMMA@SiO2 core-shell structure dispersion. The dispersion was then centrifuged sequentially. After washing and drying, PMMA@SiO2 core-shell structured powder was obtained. An ethanol-water mixed solvent was added to a beaker, and ammonia was added to adjust the pH to 9-10. After stirring for a period of time, PMMA@SiO2 core-shell structured powder was added and stirred for a period of time. Then, hexadecyltrimethoxysilane (HDTMS) was added, and a hydrolysis-condensation reaction was carried out under water bath and stirring conditions. After the reaction was completed, the reaction product was centrifuged, washed and dried to obtain HDTMS-modified PMMA@SiO2 core-shell structured hydrophobic particles, which are the PMMA@SiO2 core-shell structured hydrophobic particles with hexadecyltrimethoxysilane (HDTMS) grafted on the surface. (3) Preparation of composite coating: The WO obtained in step (1) 2.9 / CNTs composite photothermal filler is mixed with PDMS adhesive and coated on the substrate surface. After heating and drying, another layer of PDMS adhesive is coated and heated for a short time to make it semi-cured. The HDTMS modified PMMA@SiO2 core-shell structure hydrophobic particles obtained in step (2) are ultrasonically dispersed in anhydrous ethanol to obtain a coating slurry. The coating slurry is sprayed onto the semi-cured substrate surface and heated and dried to obtain the photothermal superhydrophobic anti-icing composite coating.
[0014] Further, in step (1), the WO 2.9 The carbon nanotube content in the CNTs composite photothermal filler is 15-30 wt.%; in step (2), the ratio of polymethyl methacrylate (PMMA) microspheres, tetraethyl orthosilicate (TEOS) and hexadecyltrimethoxysilane (HDTMS) is 0.1 g: (0.1-0.5) mL: (0.10-0.15) mL; in step (2), the ethanol-water mixed solvent is prepared by mixing ethanol and deionized water in a volume ratio of 8:2.
[0015] Furthermore, in step (2), the temperature of the hydrolysis-condensation reaction is 30-40℃ and the reaction time is 5-6 hours; the drying temperature is 50-70℃ and the drying time is 10-30 hours, and the drying process is carried out in a vacuum environment.
[0016] Further, in step (3), the process parameters of the spraying process are: spraying distance of 2-5cm, compressed air pressure of 0.2-0.5MPa, and spraying thickness of 20-50μm.
[0017] Furthermore, the composite coating is applied to the anti-icing treatment of power transmission lines, wind turbine blades, aircraft wings, or the surfaces of transportation vehicles; the application process is as follows: the composite coating is prepared on the target surface to be anti-iced, and under sunlight or simulated sunlight, WO 2.9 / CNTs composite photothermal fillers absorb light energy and convert it into heat energy, which raises the surface temperature of the coating and delays or melts ice buildup; at the same time, the superhydrophobic surface reduces the contact area and residence time of water droplets on the surface, thus achieving the anti-icing function in a synergistic way.
[0018] The design mechanism of this invention is as follows: To address the problems of low photothermal efficiency and poor hydrophobic stability in existing anti-icing coatings, this invention proposes a technical solution that organically combines a highly efficient photothermal conversion component with a stable superhydrophobic micro / nano structure. (The component used is non-stoichiometric tungsten oxide WO3.) 2.9 Due to its unique oxygen-vacancy structure, carbon nanotubes exhibit excellent localized surface plasmon resonance (LSPR) effects, enabling efficient light absorption and heat conversion in the near-infrared region. As a typical one-dimensional carbon nanomaterial, carbon nanotubes possess broad-spectrum light absorption characteristics, extremely high thermal conductivity, and chemical stability. Combining them with WO3... 2.9 The composite structure promises to create efficient electron transport channels and enhance light absorption, thereby achieving more efficient interfacial photothermal conversion. Simultaneously, the PMMA@SiO2 core-shell structure modified with HDTMS provides excellent film-forming properties while enabling the construction of stable micro-nano rough structures through the rigid SiO2 shell. Through this design, the coating can actively melt accumulated ice using the photothermal effect, significantly reducing the adhesion between the ice layer and the substrate, achieving a synergistic effect of passive anti-icing and active de-icing.
[0019] The advantages and beneficial effects of this invention are as follows: 1. The photothermal superhydrophobic anti-icing composite coating provided by the present invention is composed of WO4 components sequentially coated onto a substrate. 2.9 The WO is composed of a CNTs composite photothermal filler layer and a PMMA@SiO2 core-shell structured hydrophobic particle layer. 2.9 / CNTs composite photothermal filler as the photothermal conversion center, utilizing WO 2.9The oxygen vacancy defects and the broad-spectrum absorption characteristics of CNTs enable efficient solar energy capture and photothermal conversion. The PMMA@SiO2 core-shell structure is grafted with hexadecyltrimethoxysilane (HDTMS) as a hydrophobic modifier. Through hydrolysis and condensation, low-surface-energy long-chain alkyl groups are introduced, giving the coating surface superhydrophobic properties, with a water contact angle greater than 150° and a roll-off angle less than 10°. The composite coating surface has a micro-nano rough structure, achieving anti-icing functionality through the synergistic effect of photothermal and superhydrophobic effects.
[0020] 2. The photothermal superhydrophobic anti-icing composite coating of this invention has a simple preparation process, readily available raw materials, and is environmentally friendly, effectively solving the problems of low photothermal efficiency and poor hydrophobic stability of existing anti-icing coatings. This coating constructs a composite coating with a micro-nano rough structure on the substrate surface through a simple solution mixing and spraying process.
[0021] 3. This invention uses WO 2.9 / CNTs as photothermal conversion components, utilizing WO 2.9 The oxygen vacancy defects and the broad-spectrum absorption characteristics of CNTs enable efficient solar capture and photothermal conversion, solving the problem of low photothermal efficiency in existing technologies.
[0022] 4. This invention uses PMMA@SiO2 core-shell structure grafted with HDTMS as the hydrophobic component, which endows the coating with excellent superhydrophobic properties and low surface energy characteristics, and has excellent passive water repellency and anti-icing ability.
[0023] 5. The coating of the present invention, through the synergistic effect of photothermal effect and superhydrophobic effect, not only has excellent passive water-repellent and anti-icing ability, but can also rapidly heat up under light conditions and actively melt the accumulated ice through photothermal effect, significantly reducing the adhesion between the ice layer and the substrate, and realizing the synergistic effect of passive anti-icing and active de-icing.
[0024] 6. In a low-temperature environment of 0℃ to -10℃, when the light intensity is 1.0kW / m², the surface temperature of the composite coating of the present invention can rise by more than 10℃, exhibiting excellent photothermal anti-icing performance; the coating's adhesion strength to ice is reduced, resulting in good de-icing effect. Attached Figure Description
[0025] Figure 1 WO prepared in Example 1 2.9 UV-Vis-NIR spectra of CNTs composite photothermal fillers; where: (a) WO 2.9 -0~100%CNTs; (b)WO 2.9 -15%~30% CNTs.
[0026] Figure 2The infrared thermal image prepared in Example 1; wherein: (a) WO 2.9 -0~100%CNTs; (b)WO 2.9 -15%~30% CNTs.
[0027] Figure 3 The image shows the Fourier transform infrared spectrum of PMMA@SiO2-HDTMS prepared in Example 1; where, from top to bottom, they are PMMA@SiO2-HDTMS, PMMA@SiO2, and PMMA.
[0028] Figure 4 The images show the microstructure of PMMA, PMMA@SiO2 and PMMA@SiO2-HDTMS prepared in Example 1 under a scanning electron microscope; where: (a) PMMA; (b) PMMA@SiO2; (c) and (d) are PMMA@SiO2-HDTMS.
[0029] Figure 5 The static contact angle and roll-off angle of the PMMA@SiO2-HDTMS prepared in Example 1 are shown.
[0030] Figure 6 The chart shows the freezing time of bare aluminum sheets under low temperature conditions; (a) freezing time of water droplets on bare aluminum sheets at -2℃; (b) freezing time of water droplets on bare aluminum sheets at -5℃; (c) freezing time of water droplets on bare aluminum sheets at -10℃.
[0031] Figure 7 The images show a comparison of the freezing time of the composite coating prepared in Example 1 under low temperature conditions; where: (a) freezing of water droplets on the composite coating at -2℃; (b) freezing time of water droplets on the composite coating at -5℃; and (c) freezing time of water droplets on the composite coating at -10℃.
[0032] Figure 8 The melting time of water droplets on a bare aluminum sheet under -2℃ and light conditions.
[0033] Figure 9 The melting of water droplets on a bare aluminum sheet under -5℃ and light conditions.
[0034] Figure 10 The melting time of water droplets on the composite coating and infrared thermal imaging images are shown under conditions of -5℃ and light illumination.
[0035] Figure 11 The melting time of water droplets on the composite coating under -10℃ and light conditions, as well as infrared thermal imaging images. Detailed Implementation
[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0037] This invention provides a photothermal superhydrophobic anti-icing composite coating, using PDMS as a binder to bond WO4. 2.9 / CNTs photothermal filler and PMMA@SiO2-HDTMS superhydrophobic structure are layered and coated on an aluminum sheet to form a coating with photothermal + superhydrophobic composite effect (WO). 2.9 / CNTs-PMMA@SiO2-HDTMS composite coating).
[0038] The WO 2.9 The preparation method of the CNTs-PMMA@SiO2-HDTMS composite coating is as follows: CNTs and WO3 are mixed together. 2.9 WO3 was obtained by dispersing the WO3 in anhydrous ethanol in a certain proportion, followed by stirring, washing, and drying. 2.9 / CNTs composite photothermal filler. PMMA was dispersed in a mixed solvent of anhydrous ethanol and deionized water, and an ethanol solution of tetraethyl orthosilicate was added. A SiO2 shell was synthesized on the PMMA surface using the sol-gel method, yielding a PMMA@SiO2 core-shell structure. Then, PMMA@SiO2 core-shell particles were dispersed in a mixed solvent of anhydrous ethanol and deionized water, and HDTMS was added and mixed. Long-chain alkane HDTMS was grafted onto the SiO2 surface to obtain a PMMA@SiO2-HDTMS superhydrophobic structure (HDTMS-modified PMMA@SiO2 core-shell hydrophobic particles). Finally, WO3... 2.9 / CNTs are mixed with PDMS adhesive and coated onto an aluminum substrate. After drying and curing, another layer of PDMS adhesive is coated and heated briefly to semi-cur it. Then, PMMA@SiO2-HDTMS is sprayed onto the sample surface and dried and cured again to form a photothermal superhydrophobic coating.
[0039] In the following examples, when preparing the composite coating, WO 2.9 The total amount of CNTs is 20 mg; the amount of PMMA@SiO2-HDTMS is 20-40 mg.
[0040] The WO 2.9 / CNTs-PMMA@SiO2-HDTMS composite coating can be used in high-efficiency photothermal superhydrophobic anti-icing materials. Example 1:
[0041] This embodiment is a WO with high-efficiency photothermal conversion performance. 2.9 Preparation of / CNTs composite photothermal fillers and PMMA@SiO2-HDTMS microparticles with superhydrophobic and low surface energy structures. WO 2.9CNTs were mechanically mixed with water in anhydrous ethanol at a specific ratio; a SiO2 shell was synthesized using the sol-gel method under ammonia catalysis; and HDTMS was grafted onto the SiO2 surface to synthesize PMMA@SiO2-HDTMS. The specific process is as follows: (1) Weigh a certain amount of CNTs and add them to a beaker containing anhydrous ethanol. After ultrasonic treatment to disperse them evenly, add a certain amount of WO3. 2.9 Then, it is placed in an ultrasonic machine and ultrasonically treated for 10 minutes to fully disperse it. After filtration and drying, WO3 is obtained. 2.9 / CNTs composite photothermal filler. In the composite photothermal filler, the weight proportion of CNTs ranges from 0-100%.
[0042] (2) 0.1 g PMMA microspheres with a size of 100 nm were added to a mixture of 8 mL anhydrous ethanol and 2 mL deionized water. The mixture was ultrasonicated for 10 minutes and then stirred for 10 minutes on a magnetic stirrer to disperse it evenly. About 0.2 mL of ammonia was added to adjust the pH to 9.5 to obtain a PMMA dispersion. 0.3 mL of tetraethyl silicate was mixed with 1 mL of anhydrous ethanol and slowly added to the PMMA dispersion under a 30 °C water bath. The mixture was stirred at 30 °C for 6 h. After the reaction was completed, the mixture was centrifuged to obtain a wet cake. The cake was washed twice with 50% ethanol and anhydrous ethanol respectively. The wet cake was vacuum dried at 60 °C for 12 h to obtain PMMA@SiO2 core-shell structure powder.
[0043] (3) Mix 9 mL of anhydrous ethanol, 1 mL of deionized water and 0.4 mL of ammonia water to make pH≈9, stir at 40℃ for 20 min, add PMMA@SiO2 core-shell structure powder obtained in step (2) and continue stirring for 30 min, add 0.12 mL of HDTMS and continue stirring in a water bath at 40℃ for 5 h, centrifuge after the reaction is completed to obtain wet cake, wash three times with anhydrous ethanol, and vacuum dry the wet cake at 60℃ for 24 h to obtain HDTMS modified PMMA@SiO2 core-shell structure hydrophobic particles; Figure 1 WO prepared in Example 1 2.9 UV-Vis-NIR spectrum of CNTs composite photothermal filler Figure 1 (a) Shows WO3 doped with CNTs at concentrations ranging from 0% to 100%. 2.9 The absorbance curves of the material in the wavelength range of 200-2000 nm show that the absorbance is highest in the visible light region (400 nm~780 nm) when the CNT content is 20 wt.%. Figure 1 (b) Further focus on WO3 when CNT content is 15-30 wt.% 2.9The absorbance curves of CNTs composite photothermal fillers in the visible light region (400nm-780nm) show that the absorbance is highest at 15wt.%CNTs.
[0044] Figure 2 WO prepared in Example 1 2.9 Infrared thermogram of CNTs composite photothermal filler Figure 2 (a) WO3 with different CNT doping contents from 0% to 100% is shown. 2.9 The material is illuminated by a xenon lamp with an intensity of 1.0 kW / m². 2 The heating effect at 1 min, 2 min and 3 min under the conditions shows that the heating effect is the best at 20 wt.% CNTs. Figure 2 (b) A more detailed comparison was made of samples doped with 15% to 30% CNTs, comparing the temperature at three different time periods, and the heating effect was best at 15% CNTs.
[0045] Figure 3 The Fourier transform infrared spectra of PMMA@SiO2, PMMA@SiO2-HDTMS prepared in Example 1 and the raw material PMMA are shown below. By comparing the spectra of PMMA@SiO2 and PMMA, the results are obtained at 1103.77 cm⁻¹. -1 The presence of a broad, high-intensity Si-O-Si absorption band indicates successful SiO2 shell coating on the PMMA surface. By comparing the spectra of PMMA@SiO2-HDTMS with those of PMMA@SiO2 and PMMA, it can be observed that after HDTMS modification, a band at 2919.75 cm⁻¹ is observed. -1 and 2849.18 cm -1 Characteristic absorption peaks belonging to long-chain alkyl groups appeared at 1468.23 cm⁻¹. -1 The presence of methylene CH bending vibration confirms the successful grafting of HDTMS.
[0046] Figure 4 The images show the microstructure of PMMA, PMMA@SiO2, and PMMA@SiO2-HDTMS prepared in Example 1 under a scanning electron microscope. Figure 4 (a) Shows that the surface of the PMMA microspheres is smooth; Figure 4 (b) It shows that a SiO2 shell was successfully coated on the PMMA surface, forming a core-shell structure; Figure 4 (c) and Figure 4 (d) shows that after grafting HDTMS, the surface morphology of the particles did not change significantly, maintaining the nanoscale surface roughness, and the surface was obviously modified by HDTMS. This micro-nano rough structure + low surface energy modification is the key to achieving superhydrophobic properties. Example 2:
[0047] This embodiment involves static contact angle and roll-off angle testing using the PMMA@SiO2-HDTMS material prepared in Example 1. The specific process is as follows: The coating sample was placed horizontally on the sample stage of the contact angle measuring instrument. Using the pendant drop method, 4 μL of deionized water was dropped onto the coating surface. The droplet image was captured by the instrument's built-in camera, and the contact angle between the droplet and the coating surface was calculated using analysis software. Subsequently, the sample stage was tilted, and the tilt angle at which the droplet began to roll was recorded; this is the roll-off angle.
[0048] Figure 5 The static contact angle and roll-off angle of PMMA@SiO2-HDTMS prepared in Example 1 are shown. The static contact angle (WCA) of the three samples is greater than 150° and the roll-off angle (SA) is less than 10°, which confirms that the coating material has excellent superhydrophobic properties. Example 3:
[0049] This embodiment uses the WO prepared in Example 1. 2.9 / CNTs and PMMA@SiO2-HDTMS were used to prepare WO 2.9 The / CNTs-PMMA@SiO2-HDTMS composite coating underwent icing and melting tests, as detailed below: (1) Using PDMS as an adhesive, a layer of PDMS is coated on an aluminum sheet, and semi-cured by short-term heating at 60°C for 10 minutes, and then mixed with WO4. 2.9 / CNTs photothermal filler is mixed and coated on the sample surface, heated to 60℃ to fully cure it, then coated with a layer of PDMS adhesive, heated for a short time to semi-cur it, then PMMA@SiO2-HDTMS is dissolved in anhydrous ethanol and sprayed onto the sample surface using a spray gun, and then heated at high temperature again to completely evaporate the anhydrous ethanol, forming a photothermal superhydrophobic composite coating.
[0050] (2) Place the bare aluminum sheet and the sample on a freezing platform and set the temperature to -2℃, -5℃ and -10℃ respectively to test the freezing time of 10μL deionized water on the bare aluminum sheet and the sample.
[0051] (3) Keep the droplets on the bare aluminum sheet and the sample at the current set temperature under the condition that they have frozen, and test their melting time under a light intensity of 1.0 kW / m².
[0052] Figure 6 This refers to the freezing time of bare aluminum sheets on freezing platforms at -2℃, -5℃, and -10℃. For example... Figure 6 As shown in (a)-(c), water droplets rapidly freeze on bare aluminum sheets at -2℃, -5℃, and -10℃, with freezing times of approximately 1 minute, 45 seconds, and 19 seconds, respectively. In contrast, Figure 7WO prepared in Example 3 2.9 Freezing time of / CNTs-PMMA@SiO2-HDTMS composite coating on freezing platforms at -2℃, -5℃, and -10℃. For example... Figure 7 As shown in (a)-(c), the freezing time of water droplets on the composite coating is significantly extended, especially at -2℃, where there is no obvious freezing phenomenon even after 30 minutes or 40 minutes, demonstrating the excellent passive water repellency and anti-icing capability of the coating.
[0053] Figure 8-11 Bare aluminum sheets and WO prepared in Example 3 2.9 Melting time of / CNTs-PMMA@SiO2-HDTMS composite coating under low temperature (-2℃, -5℃, -10℃ frozen platform) and light conditions. Figure 8 The results showed that under -2°C light conditions, the ice on the bare aluminum sheet melted within 1 minute and 51 seconds; while Figure 9 The results showed that, at -5°C, the ice on the bare aluminum sheet did not melt even after being exposed to light for 10 minutes. Figures 10-11 The results show that, under the same light intensity, the ice on the composite coating melts in about 1 minute and 30 seconds at -5℃ and -10℃, respectively, with a melting efficiency significantly higher than that of bare aluminum sheets. In a low-temperature environment of 0℃ to -10℃, when the light intensity is 1.0 kW / m², the surface temperature of the coating material can rise by more than 10℃, demonstrating the coating's excellent photothermal active de-icing capability.
[0054] This invention utilizes the highly efficient photothermal conversion component WO 2.9 The organic combination of CNTs with the stable superhydrophobic micro / nano structure PMMA@SiO2-HDTMS not only effectively delays icing time but also enables rapid melting and de-icing under light conditions, achieving a synergistic effect between passive anti-icing and active de-icing. This coating material has a simple preparation process and readily available raw materials, effectively solving the problems of low photothermal efficiency and poor hydrophobic stability in existing anti-icing coatings. It shows broad prospects for anti-icing applications in power transmission, transportation, and new energy facilities. The above examples are for reference only. WOs that are similar to or derived from the concept of this patent are not applicable. 2.9 The CNTs-PMMA@SiO2-HDTMS composite coating and its preparation method are both protected within the scope of this patent.
Claims
1. A photothermal superhydrophobic anti-icing composite coating, characterized in that: This composite coating is composed of a filler layer and a hydrophobic particle layer sequentially coated on a substrate. The filler layer is made of WO3. 2.9 The CNTs composite photothermal filler is composed of hydrophobic particle layers made of PMMA@SiO2 core-shell structured hydrophobic particles with surface grafted hexadecyltrimethoxysilane (HDTMS); the WO 2.9 / CNTs composite photothermal filler serves as the photothermal conversion center, and hexadecyltrimethoxysilane (HDTMS) on the surface of the PMMA@SiO2 core-shell hydrophobic particles serves as the hydrophobic modifier; the surface of the composite coating has a micro-nano rough structure, and achieves anti-icing function through the synergistic effect of photothermal effect and superhydrophobic effect.
2. The photothermal superhydrophobic anti-icing composite coating according to claim 1, characterized in that: The WO 2.9 / CNTs composite photothermal filler is made of WO 2.9 It is composed of CNTs, of which WO 2.9 The WO3 is a non-stoichiometric tungsten oxide with an oxygen vacancy defect structure; CNTs are carbon nanotubes, serving as the thermally conductive framework and light absorption enhancement component of the composite coating; the WO3... 2.9 The carbon nanotube content in the CNTs composite photothermal filler is 15-30 wt.% to ensure that the coating has good photothermal heating performance.
3. The photothermal superhydrophobic anti-icing composite coating according to claim 1, characterized in that: The PMMA@SiO2 core-shell hydrophobic particles with surface grafted hexadecyltrimethoxysilane (HDTMS) have a polymethyl methacrylate (PMMA) microsphere core and a silica (SiO2) shell, with hexadecyltrimethoxysilane (HDTMS) grafted onto the surface of the silica (SiO2) shell. The size of the polymethyl methacrylate (PMMA) microspheres is 80-120 nm, and the thickness of the SiO2 shell is 10-50 nm. The thickness of the SiO2 shell is at the nanometer level and is used to construct surface roughness.
4. The photothermal superhydrophobic anti-icing composite coating according to claim 3, characterized in that: The hexadecyltrimethoxysilane (HDTMS) is grafted onto the surface of the SiO2 shell layer of the PMMA@SiO2 core-shell structure through a hydrolysis-condensation reaction, introducing long-chain alkyl groups with low surface energy, so that the coating surface exhibits superhydrophobic properties, with a water contact angle greater than 150° and a roll-off angle less than 10°.
5. The photothermal superhydrophobic anti-icing composite coating according to claim 1, characterized in that: In this composite coating, the filler layer has a thickness of 1-3 mm, and the hydrophobic particle layer has a thickness of 20-50 μm.
6. The method for preparing the photothermal superhydrophobic anti-icing composite coating according to any one of claims 1-5, characterized in that: The method includes the following steps: (1) Preparation of WO 2.9 / CNTs composite photothermal filler: CNTs are dispersed in anhydrous ethanol, and WO3 is added. 2.9 The mixture was ultrasonically stirred until homogeneous; the resulting mixture was then washed and dried to obtain WO3. 2.9 / CNTs composite photothermal filler; (2) Preparation of HDTMS-modified PMMA@SiO2 core-shell hydrophobic particles: First, PMMA@SiO2 core-shell structures were prepared by sol-gel method, and then hexadecyltrimethoxysilane (HDTMS) was grafted onto the surface of the core-shell structure by hydrolysis-condensation reaction. The specific process is as follows: polymethyl methacrylate (PMMA) microspheres were dispersed in an ethanol-water mixed solvent, and ammonia was added to adjust the pH to 9-10 to obtain a PMMA dispersion. Ethanol solution of tetraethyl orthosilicate (TEOS) was slowly added to the PMMA dispersion under water bath conditions of 25-35℃ to carry out the reaction and obtain a PMMA@SiO2 core-shell structure dispersion. The dispersion was then centrifuged sequentially. After washing and drying, PMMA@SiO2 core-shell structured powder was obtained. An ethanol-water mixed solvent was added to a beaker, and ammonia was added to adjust the pH to 9-10. After stirring for a period of time, PMMA@SiO2 core-shell structured powder was added and stirred for a period of time. Then, hexadecyltrimethoxysilane (HDTMS) was added, and a hydrolysis-condensation reaction was carried out under water bath and stirring conditions. After the reaction was completed, the reaction product was centrifuged, washed and dried to obtain HDTMS-modified PMMA@SiO2 core-shell structured hydrophobic particles, which are the PMMA@SiO2 core-shell structured hydrophobic particles with hexadecyltrimethoxysilane (HDTMS) grafted on the surface. (3) Preparation of composite coating: The WO obtained in step (1) 2.9 / CNTs composite photothermal filler is mixed with PDMS adhesive and coated on the substrate surface. After heating and drying, another layer of PDMS adhesive is coated and heated for a short time to make it semi-cured. The HDTMS modified PMMA@SiO2 core-shell structure hydrophobic particles obtained in step (2) are ultrasonically dispersed in anhydrous ethanol to obtain a coating slurry. The coating slurry is sprayed onto the semi-cured substrate surface and heated and dried to obtain the photothermal superhydrophobic anti-icing composite coating.
7. The method for preparing the photothermal superhydrophobic anti-icing composite coating according to claim 6, characterized in that: In step (1), the WO 2.9 The carbon nanotube content in the CNTs composite photothermal filler is 15-30 wt.%; in step (2), the ratio of polymethyl methacrylate (PMMA) microspheres, tetraethyl orthosilicate (TEOS) and hexadecyltrimethoxysilane (HDTMS) is 0.1 g: (0.1-0.5) mL: (0.10-0.15) mL; in step (2), the ethanol-water mixed solvent is prepared by mixing ethanol and deionized water in a volume ratio of 8:
2.
8. The method for preparing the photothermal superhydrophobic anti-icing composite coating according to claim 6, characterized in that: In step (2), the temperature of the hydrolysis-condensation reaction is 30-40℃ and the reaction time is 5-6 hours; the drying temperature is 50-70℃ and the drying time is 10-30 hours, and the drying process is carried out in a vacuum environment.
9. The method for preparing the photothermal superhydrophobic anti-icing composite coating according to claim 6, characterized in that: In step (3), the process parameters of the spraying process are: spraying distance of 2-5cm, compressed air pressure of 0.2-0.5MPa, and spraying thickness of 20-50μm.
10. The application of the photothermal superhydrophobic anti-icing composite coating according to claim 1 in the field of anti-icing, characterized in that: The composite coating is applied to the anti-icing treatment of power transmission lines, wind turbine blades, aircraft wings or transportation vehicles. The application process is as follows: A composite coating is prepared on the target surface to be protected against icing. Under sunlight or simulated sunlight, WO... 2.9 / CNTs composite photothermal fillers absorb light energy and convert it into heat energy, which raises the surface temperature of the coating and delays or melts ice buildup; at the same time, the superhydrophobic surface reduces the contact area and residence time of water droplets on the surface, thus achieving the anti-icing function in a synergistic way.